The Effectiveness of Hypnoteaching Method toward Students Speaking Anxiety - Salma Aida Maftuhah; Fitri Hilmiyati; Selnistia Hidayani (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2023)
The purpose of this study was to measure the effectiveness of hypnoteaching method reducing speaking anxiety in eleventh graders at SMA Al-Asmaniyah. The research question of this study is “How is the effectiveness of hypnoteaching method in reducing students' speaking anxiety for eleventh graders in middle school Al-Asmaniyah and the purpose of this study was